KEPEMIMPINAN STRATEJIK YANG PROFETIK MENGHADAPI DINAMIKA EKONOMI - Kuncoro, Mudrajat (Manajemen Bisnis Syariah, 2011)
The elected SBY and Boediono as President and Vice President in 2009reflects the high expectation of the people regarding the continuity and basicchange especislly in relation to response to the unfinished agendas.Since October 20 2004 , SBY has been stressing on the new deal which areexpressed in the triple tract strategy, namely : pro-growth, pro-job and propoor.The government is also formulate and implement RPJM or National MidtermDevelopment Plan to solve variety of national problems . The agendas are: 1.Creating the scure and praceful Indonesia. 2. Realize the just and democraticIndonesia. And 3. Elevating Indonesian people welfare.Strategic leadership is an ability to anticipate, to dream, to maintainflexibility and others empowerment to create expected strategic change.(Hittet.al.2001). There are three general activities by leader which will implementchange, namely : developing strategic intent, developing organization andforming corporate culture.By using the mentioned criteria, the performance of SBYs government andleadership can be analyzed and evaluated.The conclusion is that economicdevelopment is far from “quality”, this is the challenge for SBYsleaderships.There are general trends of Indonesian development plan in the past :Disregard of spatial dimension, inequality, sectoral rather than regional andunanticipated plan on several disruptions.The fact of SBY and Boediono asPresident and Vice President of Indonesia 2009 – 2014 the revival of Indonesianeconomic should not be just a myth.Keywords : leaderships, strategic, development, economic.